No need to take what you already have: perspective taking's effect on empathic concern for low-need targets. Issue 1 (2nd January 2022) - Hodges, Sara D.; Wixwat, Maria
ABSTRACT: Recent studies have (quite persuasively) challenged a previous body of work suggesting that taking the perspective of targets described as experiencing highly distressing plights would increase empathic concern for those targets. In the current study, we test whether perspective-taking might still increase empathic concern for targets in less negative predicaments. College participants (N = 303) were given either perspective-taking instructions, or no instructions, before reading posts from targets describing negative, but not terrible, experiences. Consistent with recent results challenging the effects of perspective taking, even for these low-need targets, perspective-taking instructions had no effect on empathic concern (nor on other empathic emotions). However, participants in the perspective-taking condition were more likely to reach out to the targets by writing them a note in response to the negative experience. Results are discussed in terms of perspective-taking instructions having little effect on what perspective takers feel but possibly some effect on what they do.